Prevalence of heterozygous familial hypercholesterolaemia and its impact on long-term prognosis in patients with very early ST-segment elevation myocardial infarction in the era of statins. (June 2016) - Rallidis, Loukianos S.; Triantafyllis, Andreas S.; Tsirebolos, Georgios; Katsaras, Dimitrios; Rallidi, Maria; Moutsatsou, Paraskevi; Lekakis, Jonh
Abstract: Background and aims: Familial hypercholesterolaemia (FH) is an important cause of early onset coronary artery disease. We assessed the prevalence of clinical heterozygous FH (HeFH) among patients with very early ST-segment elevation myocardial infarction (STEMI), its management and its impact on long-term prognosis in the era of widespread utilization of statins. Methods: We recruited prospectively 320 consecutive patients who had survived their first STEMI ≤35 years of age. Using the Dutch Lipid Clinic Network algorithm patients having HeFH (possible, probable or definite) were identified. Results: Sixty-five patients (20.3%) had definite/probable HeFH and 163 patients (50.9%) had possible FH. Two years after discharge among 51 patients with definite/probable HeFH and available lipid levels, 43 (84.3%) were taking statins of whom 10 (23.3%) were on high-intensity statin therapy but only 1 (2.3%) of the statin-treated patients had LDL cholesterol levels <1.8 mmol/L (70 mg/dL). After a median follow-up of 9.1 years, major adverse coronary events (MACE) occurred in 99 (38.8%) of 255 patients with available follow-up information. Definite/probable HeFH was associated with an excess risk for recurrence of MACE independently of statin use, continuation of smoking after the STEMI, hypertension, diabetes mellitus, and sex (hazard ratio = 1.615, 95% confidence interval, 1.038 to 2.512, p = 0.03). Conclusions: One out of five patients who develop STEMI ≤35 years of age has definite/probable HeFH and despite the use of statins there is a therapeutic gap and a high recurrence rate of cardiac events during long-term follow-up. Highlights: ∼20% of patients with premature AMI has clinically diagnosed heterozygous FH. Patients with FH are undertreated with currently available lipid lowering drugs. FH patients with AMI have a high recurrence rate of cardiac events. All young coronary patients should be routinely screened for FH.